Evaluation of the Effectiveness of Quantitative Easing in the United States from 2008-2022 - Ben Ahmed, Adam; Zubíková, Adéla; Ševčíková, Michaela; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2024)
The principal objective of this thesis is to scrutinise the macroeconomic effectiveness of Quantitative Easing in the United States from the aftermath of the global financial crisis to 2022. A particular focus is directed towards the examination of the transmission channels inherent to Quantitative Easing, delineating the mechanisms through which it exerts influence on macroeconomic variables such as inflation or unemployment. In the theoretical part the focus is directed towards the rationale and the context of Quantitative Easing as well as the transmission channels through which Quantitative Easing exerts influence on the aggregate economic performance and instigates economic activity. The practical part relies on a graphical analysis complemented by a Vector Autoregressive model for a thorough examination. The empirical evidence suggests that the asset purchase programmes might have provided a modicum of support to the financial sectors and mitigated deflationary risks. However, their impact on the broader economy and its performance might be markedly constrained. Through this detailed analysis, the study tries to illuminate the complex ramifications of Quantitative Easing and aims to furnish some contribution to the academic and policy-making dialogue concerning its application in monetary policy, with objective and data-based insights.
Vedoucí práce: Adéla Zubíková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses